The Indonesian Version of SF-36 Questionnaire: Validity and Reliability Testing in Indonesian Healthcare Workers Who Handle Infectious Diseases - Berliana Devianti Putri; Nur Septia Handayani; Sahra Zafhira Ekayafita; Ajeng Dilla Lestari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Quality of life is a parameter to measure the position of life for high-risk people, including healthcare workerswho handle infectious disease. Quality of life affects productivity and performance. A lot of instrumentscan be used to measure the quality of life, which one is the 36-item Short From Health Survey (SF-36). Itis an international standard questionnaire which measuring health-related quality of life, so a translationprocess into Indonesian is necessary. The aim of this study is to evaluate the validity and reliability of SF-36questionnare on Indonesian version. This study was an observational analytic with a cross-sectional design.This study divided into 2 stages, ie. translating questionnaire into Indonesian version, then testing it withrespondents. We evaluated 45 healthcare workers working in the COVID-19 isolation room. Data weretaken from September to October 2020. This study was analyzed by Pearson Correlation and Cronbach’alpha with ?=5% and using SPSS v.23 software. Results showed that the overall cronbach’ alpha coefficientwas 0.883, while the five dimensions were >0.70 (physical function, vitality, mental health, bodily pain,and general health). But, the role physical, role emotional, and social function dimensions had cronbach’alpha coefficient 0.6-0.7. The Indonesian version of SF-36 was valid and reliable, so it could be used as ainstruments for measuring health related quality of life among healthcare workers who handle infectiousdiseases, especially in COVID-19.